2024
DOI: 10.1037/ser0000765
|View full text |Cite
|
Sign up to set email alerts
|

Prosumers’ experiences of stigma dimensions within the clinical psychology field.

Abstract: Lived experiences of mental illness and stigmatizing attitudes toward psychiatric diagnoses are common throughout the world. Research demonstrates that clinical psychologists are not exempt from having lived experiences of mental illness, nor experiencing, witnessing and perpetuating stigma. However, no research has examined prosumers' (providers and consumers of mental health services) experiences of witnessing discrimination within the field of clinical psychology. The purpose of this study was to explore pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This might highlight social acceptability surrounding the perpetration of stigma within clinical psychology and align with previous research findings that mental health professionals often reject and participate in the social isolation of individuals experiencing mental illness (Wahl, 2012). A prior analysis of qualitative data from the present study's sample indicated that prosumers' self-reported stigma may also vary depending on diagnosis; prosumers described holding more negative attitudes toward borderline personality disorder, schizophrenia, and bipolar disorder than depression and anxiety disorders (Lo ´pez-Aybar et al, 2023).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This might highlight social acceptability surrounding the perpetration of stigma within clinical psychology and align with previous research findings that mental health professionals often reject and participate in the social isolation of individuals experiencing mental illness (Wahl, 2012). A prior analysis of qualitative data from the present study's sample indicated that prosumers' self-reported stigma may also vary depending on diagnosis; prosumers described holding more negative attitudes toward borderline personality disorder, schizophrenia, and bipolar disorder than depression and anxiety disorders (Lo ´pez-Aybar et al, 2023).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, prosumers have been found to endorse low levels of internalized stigma in previous studies (Kazemsoltani, 2017; Tay et al, 2018). In a grounded theory analysis observing prosumer experiences with internalized stigma, López-Aybar et al (2023) found that prosumers describe experiences of internalized stigma directly related to their role or identity as clinical psychologists, specifically in terms of questioning their own competence to meet the demands of their roles as clinical psychologists. In the present study, the questionnaire chosen to evaluate internalized stigma did not ask questions pertaining to prosumers’ identity as a provider with an assigned diagnosis.…”
Section: Discussionmentioning
confidence: 99%